George Friedman, The Next Decade: Empire and Republic in a Changing World, Kraków 2012 - Galewska, Iwona (The Copernicus Journal of Political Studies, 2018)
Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14762